Protagonisti socialne geografije - Gosar, Anton (Geografski vestnik, 2021)
In geography of the 20th century, the interpretation of the existing spatial reality experienced different research approaches and definitions. Geographers came to the conclusion that society, man and social groups play also an important role in the contemporary appearance and function of a region. The path to such a belief has been paved before WW2 by several geographers in Europe and North America. Following the Austro-German model this theory and research methodology was in Yugoslavia advocated predominantly by Slovene geographers, while others – mainly due to the almost exclusive denial of the spatial physical-geographical factors – opposed it. Vladimir Klemenčič, the initiator of social geography thought in Slovenia, and Svetozar Ilešič, an advocate of the unified/regional geography, stood on opposite banks with like-minded people.
Keywords: družbena geografija; geographical theory; history of geography; Slovenia; Slovenija; social geography; socialna geografija